Comparison of the retinal modulation transfer function between amblyopes successfully corrected and normal subjects - Huang, Xiao-Ming; Xu, Xue-Gu; Xu, Guo-Xing (International journal of ophthalmology, 2011)
AIM:To analyze the retinal modulation transfer function between amblyopes whose visual acuity was corrected to 5.0 and normal subjects at the same age.METHODS: RM-800 used to detect contrast sensitivity was adopted to measure MTF of 96 amblyopes (96 eyes) whose visual acuity was corrected to 5.0 and 80 normal controls (80 eyes) at the same age under six interference fringes (IVA= 0.06,0.1,0.2,0.4,0.6,0.8).RESULTS: The functional values of amblyopes were significantly lower than those of normal subjects in every fringe (P<0.01),especially in medium and high frequency.CONCLUSION:For amblyopes,MTF was still abnormal after stopping the treatments.